Spss statistics for dummies - Salcedo, Jesus; McCormick, Keith (Indianapolis : John Wiley and Sons, 2020)
"If you're involved in research, marketing, data mining, or academics, you probably know how useful SPSS (Statistical Package for the Social Sciences) can be. Here's the guidebook that will get you up to speed on SPSS 27 before you know it. A wealth of upgrades makes SPSS 27 even more valuable, and these authors, who share 55 years of experience working with and teaching SPSS, walk you through every one. You'll master the revised interface, discover some new functions, build graphs, explore advanced data analysis tools, and much more" --
Includes index.
Keywords: SPSS (Computer file); Social sciences -- Statistical methods -- Computer programs; Social sciences -- Statistical methods -- Computer programs -- Handbooks, manuals, etc; Statistics -- Data processing